The Knowledge Gap in Economics: What Does the Public Know about the Economy and What Do Economists Know about the Public? - Erwin Dekker; Pavel Kuchař (Œconomia, 2024)
Economics is characterized by a knowledge gap—a discontinuity between everyday and scientific understandings. An extensive empirical literature proves the so-called economic ignorance of the public. This has contributed to a disdain for the public among economists and provided an argument for more influence of experts. At the same time, many citizens have grown skeptical of scientific expertise, and economic expertise in particular. We question the supposed economic illiteracy of the public by pointing out serious methodological issues with the empirical literature on the economic knowledge of laypeople. Rather than seeking to meet laypeople on their own terms and in their own language, it instead tests their knowledge of (expert) concepts in academic language. More broadly, this literature assumes there is one body of economic knowledge to which some have access and others do not. We argue that economic knowledge is better understood as the multiple heterogeneous bodies of knowledge associated with different communities of practitioners. We argue that economics as a discipline should seek convergence between these bodies of knowledge through translation efforts. We demonstrate that Philip Wicksteed and Elinor Ostrom made efforts to further this convergence and suggest further constructive steps following methodological work in sociology and surveys of public understanding of economics based on interpretivist approaches. We argue that an economics which recognizes these multiple bodies of knowledge, and which aims at convergence, has the potential to improve economics education, foster mutual understanding between economists and the public, and remedy some of the mutual distrust between them.